Investigating consequences of non-synonymous Single nucleotide polymorphisms of the Zyxin gene on protein structure and functions in Nigerian indigenous and Nera black chickens Zyxin - Sunday, Adenaike Adeyemi; Olusola, Peters Sunday; Olusesan, Fafiolu Adeboye; Adetunji, Waheed Abdullai; Aireabakhame, Abdulrahman Taofeek; Ogagaoghene, Agaviezor Brilliant; Kubura, Agbalaya Khadijah; Ndubuisi, Ikeobi Christian Obiora (Acta Scientiarum. Animal Sciences, 2025)
Zyxin functions as a regulator of the restructuring of the actin cytoskeleton during the process of repairing tissue damage, cell movement and attachment. It has also been identified as a potential gene involved in chicken coccidiosis. In order to gain a deeper understanding of these phenomena, we employed a collection of computer-based techniques and databases to examine the amino acid sequence, structural dynamics, molecular interactions, and activities of the gene. Our analysis revealed that Zyxin contains two non-synonymous SNPs (A > C at position 22 and G > A at position 137) at exon 1. Also, there existed a non-synonymous SNPs in Exon 3 (A>C and A>T both at position 861) of the gene with Synonymous SNPs observed only in exon 3 (A>G at position 812 and 854, T > C at position 863). The genetic diversity revealed in these chicken populations indicates the presence of genetic variation, with Naked neck chickens showing a considerably higher frequency of particular SNPs. Two non-synonymous single nucleotide polymorphisms (nsSNPs) were forecasted to exert a profound influence on the structure, stability, and activities of Zyxin, thereby heightening the vulnerability to coccidiosis.